The Pile of Bodies in Graphic Narratives: Variations on an Image - André Cabral de Almeida Cardoso (Ilha do Desterro)
The aim of this paper is to investigate a recurring image in graphic novels published from the 1980s to the present day: that of a pile of bodies on which the protagonist or another character in the narrative is placed. Variations on this image point to important representations of the body and personal identity in our society. They also problematize our perceptions of ourselves, of the world around us, and of our own memories. By comparing some of them, I will explore the tensions and contradictions present in these representations, and examine the ways in which they can lead to an expression of utopian desires.